2006
DOI: 10.1051/parasite/2006133231
|View full text |Cite
|
Sign up to set email alerts
|

The sera from individuals suffering from cutaneous leishmaniasis due toLeishmania braziliensispresent antibodies against parasitic conserved proteins, but not their human counterparts

Abstract: Summary :Sera from individuals suffering from leishmaniasis have been shown to strongly react against conserved proteins from the parasite, such as ribosomal, histones and heat-shock proteins. Some of these proteins have also been described as immunogenic in several auto-immune syndromes, and the detection of antibodies against them is considered to be indicative of disorder of the immune system. In this paper, we investigate whether there is any relationship between the recognition of some conserved proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Several previous works demonstrated that histone, specially H2B and H4, show antigenicity activity and were recognized by antibodies (110), apart from being upregulated when treated with sodium antimony gluconate (SAG) (111). The presence of anti-H2B antibodies has been found in symptomatic visceral and cutaneous leishmaniasis patients (112,113), corroborating that histones are needed for the correct development and survival of the parasite. Additionally, this indicates that the Ld17_v01s1_485484-485505_miRNA (form L. donovani ), which co-expresses with histone H2B, may play an important role in the regulation of parasite’s development and survival in hosts by regulating histones and other proteins.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Several previous works demonstrated that histone, specially H2B and H4, show antigenicity activity and were recognized by antibodies (110), apart from being upregulated when treated with sodium antimony gluconate (SAG) (111). The presence of anti-H2B antibodies has been found in symptomatic visceral and cutaneous leishmaniasis patients (112,113), corroborating that histones are needed for the correct development and survival of the parasite. Additionally, this indicates that the Ld17_v01s1_485484-485505_miRNA (form L. donovani ), which co-expresses with histone H2B, may play an important role in the regulation of parasite’s development and survival in hosts by regulating histones and other proteins.…”
Section: Discussionmentioning
confidence: 74%
“…Several previous works demonstrated that histone, specially H2B and H4, show antigenicity activity and were recognized by antibodies (110), apart from being upregulated when treated with sodium antimony gluconate (SAG) (111). The presence of anti-H2B antibodies has been found in symptomatic visceral and cutaneous leishmaniasis patients (112,113), corroborating that histones are needed for the correct development and survival of the parasite.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Antibodies specific for parasite histones, obtained from dogs with visceral leishmaniasis, react against Leishmania H2A [6], H3 [7], H2B and H4 [8] but do not recognize mammalian histones. Antibodies in sera from patients with cutaneous or mucocutaneous leishmaniasisis also recognize parasite histone H1 but not the human counterpart [9]. Regarding the T cell immunogenicity of parasite histones, recombinant versions of H2B [10] or H2A [11] induced IFN-γ secretion upon stimulation of PBMCs obtained from cutaneous leishmaniasis patients.…”
Section: Introductionmentioning
confidence: 98%